The Impact of Blended Learning Using Ideas Box on the Development of Critical Thinking among Syrian Students in Jordan - Asmaa Alkhatib; Suhir Jaradat (Deanship of Scientific Research (DSR), the University of Jordan, 2022)
The study aims to identify the impact of blended learning using Ideas Box in developing critical thinking among female students of non-formal education in light of the Syrian refugee crisis in the host communities in Jordan. The study followed a quasi-experimental approach. The study sample consisted of (30) female students of non-formal education, enrolled in the program to enhance the culture of dropouts at Jahd Center for Social Support in January 2020. An experimental sample consisting of (15) female students was taught the Pillars of Islam unit using Box Ideas method. A control group consisting of (15) female students was taught in a usual way. The results showed that there are statistically significant differences between the two groups in favor of the experimental group in the degree of critical thinking due to blended learning based on Ideas Box. The researchers recommend reconsidering the design of the program to enhance the culture of dropouts to include the activation of Ideas Box method in a systematic, organized and deliberate manner.